Pulmonary sarcoidosis with arterial involvement - Souza da Paz, Adriane; Coelho, João Carlos; Melo, Bartira; Pedreira, Ana Luísa; Barreto Santiago, Mittermayer (Autopsy and Case Reports, 2021)
Necrotizing sarcoid granulomatosis (NSG) is a rare and under-recognized cause of granulomatous disease, described as a variant of typical nodular sarcoidosis. It can be asymptomatic when the patient has a single pulmonary nodule or may be accompanied by cough, fever, and dyspnea, or even symptoms due to the involvement of other organs such as the eyes, liver, and central nervous system. The histopathological analysis is essential for the differential diagnosis of other infectious and non-infectious causes of granuloma and to determine the appropriate treatment. NSG is characterized by the presence of a granuloma with extensive coagulative necrosis associated with the occurrence of vasculitis. We present the case of a patient diagnosed with NSG who had an unusual outcome with recurrent pulmonary thromboembolisms followed by hemodynamic instability and death.